Dr. Jose Cortes — Deep Plane Facelift — Mexico City - Cortes, Jose (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Jose Cortes, practicing in Mexico City, Mexico. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003374; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; mexico; mexico city